Changes in water turnover and its components over one athletic season: An observational study among athletes from different sports - Jesus, F.; Francisco, R.; Bernardino, A. V.; Nunes, C. L.; Dickinson, S. L.; Rocha, P.; Minderico, C. S.; Sardinha, L. B.; Schoeller, D. A.; Silva, A. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2026)
Background : Water turnover (rH 2 O) is related to water balance including preformed water intake (WI), metabolic, inspired, and transcutaneous water. Literature is scarce on athletes. This study aimed to estimate and compare rH 2 O and its components during one athletic season (preparatory and competition phases), adjusting for body composition and energy expenditure (EE). Methods : This longitudinal observational study included 112 athletes (19.8 ± 4.9 years, 39 females). Doubly labeled water determined total EE, rH 2 O, and the remaining components through specific equations. Total body water was determined by deuterium dilution and fat-free mass by the four-compartment model. Resting EE was assessed by indirect calorimetry. Results : During the preparatory phase, male athletes showed higher rH 2 O [5.03 (0.14) kg/day] compared with females [3.64 (0.19) kg/day, p < .001], even adjusting for body mass ( p = .024), but not for fat-free mass, total body water, and EE. Triathletes showed higher values of rH 2 O after adjustments ( p < .05). Over the athletic season, no changes occurred for rH 2 O or preformed WI within or between sexes or sports, even adjusting for body composition while some changes occurred adjusting for EE ( p < .05). Over the season, metabolic water increased ( p < .001), while inspired and transcutaneous water showed both increases and reductions ( p < .05). A small prevalence (*16%) of low WI (WI * 35 ml/kg of body mass/day) was persistent in both timepoints. Conclusion : While rH 2 O and preformed WI did not differ over the season, cross-sectional differences were observed between sports but not between sexes, highlighting the variability of rH 2 O and impact of contributing factors. Low preformed WI was present throughout the athletic season.